PENGARUH LABA KOTOR, LABA OPERASI, DAN LABA BERSIH DALAM MEMPREDIKSI ARUS KAS DI MASA MENDATANG (Studi Empiris Perusahaan Manufaktur di Bursa Efek Indonesia) - Alifatur Akbar Alamsyah; Noor Shodiq Askandar (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study discusses gross profit, operating profit and net income in predicting future cash flows. The data used in this study is secondary data, consisting of companies engaged in manufacturing that have carried out operations regarding the year of research to become participation in this study, while the research sample taken is a company that has been engaged in manufacturing which has been operating for 2012 - 2017 The sampling technique is done using the purposive sampling method. The analytical tool used is multiple linear regression which produces a model Y = 0.815+ 1.096 X1 - 0.411 X2 + 0.196 X3. Normality test using kolmogorov-smirnov, classic assumption test consisting of multicollinearity, heteroscedasticity and autocorrelation. Hypothesis test using F test, coefficient of determination, and T test. The results of this study indicate that simultaneously and partially gross profit, operating profit and net income to future cash flows with a determination coefficient of 0.539 or 53.9%. This means that the contribution of gross profit, operating profit, and net income to cash flow is 53.9%, while 46.1% is a contribution from other variables not discussed in this study.Keywords: gross profit, operating profit, net income, future cash flows